Florística e estrutura da floresta de terra firme como instrumento de gestão ambiental do Parque Estadual do Utinga, Belém, Pará, Brasil - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2023)
Urban Conservation Units are essential for maintaining biodiversity and the quality of life of populations. The research aimed to know the floristic composition and structure of a stretch of dense rainforest in the lowlands (terra firme forest) of the Utinga Camilo Viana State Park. Plots were implanted inside three forest fragments of a dense lowland rain forest locally known as “terra firme forest”. The species were identified in the field by specialized technicians. The abundance of individuals and species richness and diversity were compared using the analysis of variance test; multivariate dispersion Analysis (PERMDISP) and principal coordinate analysis (PCoA) were performed using the Vegan package in R version 4.0.4 (www.r-project.org). 49 families, 123 genera, 197 species and 1,374 individuals and tree life forms were registered, liana and palm trees having the arboreal life form (94% of the total), while lianas and palm trees with only eight and four species represent only 4% and 2% of the total. Fabaceae, Burseraceae, Urticaceae, Myristicaceae and Sapotaceae were abundant in individuals, while Fabaceae, Sapotaceae, Lauraceae, Burseraceae and Chrysobalanaceae were rich in species. The flora of the Utinga State Park must be conserved mainly in the forest fragments due to the high degree of heterogeneity.
Floristics and structure of terra firme forest as an environmental management tool in the Utinga State Park, Belém, Pará, Brazil
Keywords: Biodiversidade; Unidades de Conservação; Forma de vida; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA